Pengaruh Model Team Games Tournament Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VIII SMP Negeri 1 Pangururan Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Pebrianti Nababan (LPPM Politeknik Pratama, 2023)
The purpose of this research is to determine the positive and significant influence of the Team Games Tournament Model on the Learning Motivation of Christian Religious Education and Character of Class VIII Students of SMP Negeri 1 Pangururan, Samosir Regency, Study Year 2023/2024. The research method used is a quantitative descriptive inferential method. The population was the total number of Protestant Christian students in class VIII at SMP Negeri 1 Pangururan, totaling 191 people and a sample of 49 people was determined using the Random Sampling technique. Data was collected using a positive closed questionnaire with 32 items, namely 16 items for variable Negeri 1 Pangururan, Samosir Regency, 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test, obtained a value of rxy = 0.563 > rtable(=0.05,n=49) = 0.281. b) Testing a significant relationship obtained a value of tcount= 4.667 > ttable(=0.05, dk=n-2=47)= 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=